Hubungan Minat Kejuruan Dan Motivasi Belajar Dengan Hasil Belajar Siswa Pada Mata Pelajaran Sistem Sasis Sepeda Motor Kelas XI TSM Di SMK Negeri 4 Medan: Relationship between Vocational Interest and Learning Motivation with Student Learning Outcomes in the Subject of Motorcycle Chassis System Class XI TSM At SMK Negeri 4 Medan - Ronaldo Pratama Sijabat; Riski Elpari Siregar (Universitas Pendidikan Ganesha, 2026)
This study aims to determine the relationship between vocational interest and learning outcomes of the chassis system subject of class XI TSM students of SMK Negeri 4 Medan, to determine the relationship between learning motivation and learning outcomes of the chassis system subject of class XI TSM students of SMK Negeri 4 Medan, to determine vocational interest and learning motivation towards learning outcomes of the chassis system subject of class XI TSM students of SMK Negeri 4 Medan, as input material for reference sources for other researchers in conducting research in the same field, and as input material for educational institutions in efforts to improve the quality of education. The subjects of this study were 33 class XI students. The instruments used in this study were questionnaires on vocational interest, learning motivation, and learning outcomes, data taken from the results of the mid-semester exam scores worked on by class XI students in the chassis system subject. The data analysis techniques used were Qualitative and Quantitative, Qualitative in the form of descriptive analysis and Quantitative in the form of calculating data on the relationship between vocational interest and learning motivation with student learning outcomes. From the results of data analysis, it was obtained that there is a significant relationship between Vocational Interest and Learning Outcomes. The higher the student's interest in the chosen vocation, the higher the learning outcomes achieved. Furthermore, there is no significant relationship between Learning Motivation and Learning Outcomes partially. However, learning motivation remains an important factor that drives the learning process. and there is also a significant relationship simultaneously between Vocational Interest and Learning Motivation with Learning Outcomes. These two variables together can explain the variation in student learning outcomes.